Indigenous Land Rights and Human Rights Violations in Papua: A Case Study of Land Grabbing and Corporate Exploitation (Contemporary Issues on Indonesian Human Rights Law and Policy, 2024)
This paper examines the human rights violations linked to land grabbing and corporate exploitation in Papua, Indonesia, with a specific focus on the impact on indigenous land rights. Indigenous Papuans face significant challenges in securing their ancestral lands from encroachment by multinational corporations engaged in resource extraction, including mining and agriculture. The research provides a critical analysis of the legal and regulatory frameworks that govern land rights in Papua, highlighting the gaps in enforcement and the role of both the Indonesian government and corporate actors in facilitating these violations. Using case studies from Papua’s resource-rich regions, the paper documents instances of forced displacement, environmental degradation, and violent conflicts over land ownership. It also explores the complicity of local authorities in enabling these abuses and the marginalization of indigenous voices in land governance decisions. The study draws on international human rights law, including the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), to argue for stronger protections for indigenous land rights. The paper concludes with policy recommendations aimed at ensuring better legal recognition of indigenous territories, increasing community participation in decision-making processes, and holding corporations accountable for human rights violations.